An Online Latin Poetry Translation Lab in an Italian Classical High School - Landi, Licia (IALLT Journal of Language Learning Technologies, 2003)
This paper is an account of a project on the strategy for technologybased course development and management adopted for teaching a 4th -year Latin poetry class in an Italian Oassical High school. It focuses on a strategy for course design, online delivery, and integration with an e-mail discussion list. The examples focus on Latin poetry, and there is a discussion of how technology can couple with changes in pedagogy and increase learning productivity, even in traditional subjects, when learners become self-motivated, selfdirected, and collaborative participants in their learning experience.